Differentiating Iron Deficiency Anemia from Beta-Thalassemia Trait Using Red Cell Indices: A Cross-Sectional Study (KYAMC Journal, 2026)
Background: Anemia, particularly iron deficiency anemia (IDA) and beta-thalassemia trait (βTT), is a prevalent health issue worldwide, especially in resource-limited settings like Bangladesh. Accurate differentiation between these two conditions is vital for effective management, as they have distinct pathophysiologies and treatment protocols.Objectives: This study is aimed to evaluate the reliability of red cell indices derived from automated cell counters to distinguish between IDA and βTT, thereby reducing the need for more invasive and expensive diagnostic methods.Materials and Methods: A total of 150 patients with microcytic hypochromic anemia were included in a cross-sectional analytical study conducted at the Department of Hematology, Dhaka Medical College Hospital. Using automated parameters, eight discrimination indices were calculated. Confirmatory diagnoses were made through hemoglobin electrophoresis and serum iron profiles. Sensitivity, specificity, and predictive values for each index were computed.Results: The study identified 60% of the patients as βTT and 40% as IDA. The best-performing indices for differentiation were the Green and King index (94% correct identification), followed closely by the Red Cell Distribution Width Index (RDWI, 93.33%). RBC count and Mentzer index showed similar performance (87.33%). Both RBC count and RDWI demonstrated 100% sensitivity in detecting IDA. Sensitivity, specificity, and predictive values varied significantly among indices, with the Green and King index exhibiting the highest overall accuracy.Conclusion: This study concludes that red cell indices are effective tools for differentiating between IDA and βTT in resource-constrained settings, facilitating timely and appropriate management. Further studies with larger sample sizes are recommended to validate these findings and enhance diagnostic protocols.